Technology Dependence in Educational Practice: Evaluating the Scientific and Practical Impacts. - Byrne, Matthew D. (Nursing Education Perspectives (Wolters Kluwer Health))
The article focuses on the implications of emerging technologies, particularly artificial intelligence (AI) and digital tools, on cognitive development and clinical practice in nursing education. It highlights a 2025 Harvard study that found reliance on AI and web searches may create "cognitive debt," potentially diminishing critical thinking and independent problem-solving skills essential for nursing students. While technology dependence poses risks to neurocognitive growth, certain clinical tools like smart pumps and electronic health records improve patient safety by reducing human error in medication administration. The article emphasizes the need for ongoing evaluation of technology use in education and practice to balance its benefits as tools without becoming detrimental cognitive crutches.